PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERBASIS PENDEKATAN INVESTIGASI BERBANTUAN E-LEARNING DENGAN APLIKASI MOODLEPADA SUBPOKOK BAHASAN TRIGONOMETRI KELAS X SMA - Rohmatullah, R; Dafik, D; Slamin, S (Department of Mathematics Education , University of Jember, 2013)
Abstract.The research aims toknow process and result of developing of mathematics learning intruments based on investigation approach and assistede-learning with LMS Moodle fortrigonometry topic at tenthgrade ofseniorhigh school. The research development modle refers to4D Thiagarajan models. The subject of research is students of X2 class SMAN Rambipuji in even semester academic year 2012-2013. The data of research are obtained by validation sheet, observation sheet of teacher and students activities, questionnaire, and evaluation test.Theproduct of thisresearch are lesson plan, student handbook, worksheet, evaluation test, and e-learning site.The result shows that the learning instrumentsqualifies validity, practical, and effective criteria. Key Words:Investigation approach, e-learning, LMS Moodle, trigonometry